(untitled) (Management and Connections Journal, 2026)
We identified how Brazilian research analyzes and discusses the main barriers faced by women in their professional careers through a systematic review based on the protocol of Cronin et al. (2008), considering the metaphors of the glass ceiling, sticky floor, and glass labyrinth during the period from 2014 to 2024. The selection of articles was carried out in Brazilian journals classified as higher than B2 in the Qualis system, in the field of Business. We analyzed 44 articles, and the results revealed that the glass ceiling is the most studied concept. So, despite the growth in research on the topic, there is still a lack of studies on the sticky floor and the crystal labyrinth, indicating that Brazilian research on the subject has prioritized investigations into leadership positions while neglecting other dimensions. This may reflect a limited view of the multiple obstacles women face in their professional paths.